Upaya Menjaga Nilai Luhur Pancasila dari Penyimpangan di Era Globalisasi di Kalangan Mahasiswa - Intan Cendra Kasih; Mutiara Ramadhani Teguh; Supriyono Supriyono (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2026)
Pancasila was born from the struggle of the nation’s founders, who are known as The Founding Fathers. However, in the era of increasingly widespread globalization, the noble values of Pancasila often face major challenges, especially among university students. Globalization brings rapid changes in technology, culture, communication, and lifestyle, which can influence students’ attitudes, behavior, and understanding of national identity. These changes can either strengthen or weaken the understanding of national values if not properly addressed. This study aims to analyze efforts that can be made to maintain the noble values of Pancasila from deviations in the era of globalization among students. This research uses a qualitative method, as explained by Creswell (1998), which is an approach to understanding social phenomena and human problems. In facing globalization, it is very important to maintain the noble values of Pancasila among students so that they continue to uphold morality, unity, justice, tolerance, and responsibility. Several efforts that can be made to strengthen these values include education, wise use of technology, and increasing social awareness in daily life as part of national character building.